Explaining Crimmigration in Indonesia: A Discourse of the Fight Against People Smuggling, Irregular Migration Control, and Symbolic Criminalization - Akbari, Anugerah Rizki (Indonesia Law Review, 2015)
Controlling migration in the world's largest archipelago brings various challenges to Indonesian authorities that differ from other countries. The difficulties become even more complicated since Indonesia has been known as the most favorite transit country for people who want to migrate to Australia due to its strategic geographical location, which is situated between the continents of Asia and Australia and between the Pacific and Indian oceans. Following this, the decision of choosing the mechanism of criminal law to deal with irregular migration from the start leads Indonesia to its acknowledgment as a country who is vulnerable to the trend of crimmigration. The criminalization of immigration-related conducts, the authorization of investigative power to the immigration officers, and the implementation of the 'selective policy' in the very first Immigration Law (Law No. 9/1992) justify the underlying situation in Indonesia. This condition is even harsher when Indonesia joined the fight against people smuggling since the new law concerning immigration (Law No. 6/2011) also increase criminal sanctions for immigration-related offenses. Nonetheless, this punitive approach stands as a symbolic strategy, which is barely enforced by the Indonesian authorities and it serves nothing than responding the problems with erroneous actions. By doing this, the Indonesian government has shown its weaknesses and inabilities to control crime problems to an acceptable level.